A rapid hemostatic sponge based on large, mesoporous silica nanoparticles and N-alkylated chitosan. Issue 43 (26th October 2018) - Chen, Zihao; Han, Lei; Liu, Changjun; Du, Yu; Hu, Xiao; Du, Ge; Shan, Chao; Yang, Kun; Wang, Chunlai; Li, Minggao; Li, Fan; Tian, Feng
Abstract : Due to the designed, coagulation-promoting microstructure, a rapid and safe hemostat was developed and its hemostatic efficiency was evaluated by in vitro clotting tests and in vivo hemostatic analyses. Abstract : Rapid bleeding control is increasingly important in current civilian and military emergency medicine, but the rapid hemostasis achieved with current hemostatic products is often unsafe. In this study, mesoporous silica nanoparticles (MSNs) with large pores were coordinated with a glycerol-modified N -alkylated chitosan sponge (GACS) to develop a rapid and safe hemostatic sponge. Due to its coagulation-promoting structure, MSN–GACS exhibited unique hemostatic potency in serial in vitro coagulation tests. In addition to enhanced platelet adhesion and whole blood absorption, MSN–GACS exhibited better biocompatibility than Combat Gauze (CG), which is popular in the US military. Furthermore, in rabbit femoral artery and liver injury in vivo models, MSN–GACS showed better hemostatic efficiency and lower cardiovascular toxicity than CG. In conclusion, MSN–GACS is an excellent prehospital hemostatic agent for first-aid applications.